RB1 Germline Variant Predisposing to a Rare Ovarian Germ Cell Tumor: A Case Report - Gelli, Elisa; Fallerini, Chiara; Valentino, Floriana; Giliberti, Annarita; Castiglione, Francesca; Laschi, Lucrezia; Palmieri, Maria; Fabbiani, Alessandra; Tita, Rossella; Mencarelli, Maria Antonietta; Renieri, Alessandra; Ariani, Francesca (Frontiers in Oncology, 2020)
Malignant ovarian germ cell tumors (MOGCTs) are neoplasms of the ovary, of which, due to their rarity and heterogeneity, few is reported about genetic background and development. Here, we report a 18-years old patient diagnosed with an ovarian mixed germ cell tumor, without any previous history of malignancies, who has been treated with surgery and chemotherapy and died four years later due to peritoneal metastasis complications. Patient’s blood DNA was screened for a panel of 52 cancer-related genes in order to identify predisposing aberrations to this rare cancer. The analysis discovered the uncharacterized c.2393G>A variant in RB1, the retinoblastoma gene, leading both to a missense change and a splicing perturbation of the RB1 transcript. The variant was found to be hypomorphic, damaging the C-terminal domain with a partially impaired protein function. The variant is inherited from the unaffected mother. Due to an imprinting mechanism, the maternal allele is ~3 fold more expressed than the paternal one. The parent-of-origin effect combined with the hypomorphic impact of the variant determines a rescue of sufficient tumor-suppressor activity to prevent retinoblastoma development but can predispose to other cancers in the adult age. In order to understand the somatic events acting on the germline predisposition we used the NGS-liquid biopsy covering 77 cancer driver genes. Using this approach, we detected deleterious mutations in TP53, SMAD4, FGFR3 and MSH2, indicative of a dis-regulation of cell cycle and DNA repair mechanisms pathways. In conclusion, we have pinpointed for the first time that an RB1 leaky variant, not leading to retinoblastoma because of its maternal origin, can predispose in adults to a very rare form of ovarian cancer and that the somatic disruption of few genes contributes to the tumor progression and aggressiveness.